EFEKTIVITAS TERAPI LATIHAN KESEIMBANGAN TERHADAP SKOR FAAM PADA PASIEN DENGAN INSTABILITAS KRONIS PASCA CEDERA AKUT ANKLE SPRAIN : TINJAUAN SISTEMATIS - Vania Millenia Melinda (2022)
Ankle injuries are still prone to occur and repeated ankle injuries will result in chronic instability and/or CAI (Chronic Ankle Instability). CAI is a major problem in the life of athletes, the cause of CAI is not only damage to the ligament structure but disturbances of mechanoreceptors in the joint capsule and surrounding tissue so that balance exercise therapy is needed to become an alternative rehabilitation therapy that cannot be performed surgically. Balance exercise therapy in chronically unstable patients can improve functional and postural balance. So far, to the best of the researcher's knowledge, there is still controversy over the consensus on the appropriate and structured treatment of balance exercise therapy, therefore the researcher conducted a systematic review study that aims to determine effective balance exercise therapy based on the FAAM score. This research was conducted by conducting database Pubmed, Science Direct, Scopus and using the PRISMA-P 2020 protocol with the inclusion criteria defined and re-selected with a critical review of JBI and NHLBI. The results showed that various types of balance exercise therapy were effective after the intervention based on the FAAM score. Balance exercise therapy on FAAM scores performed after the intervention showed improvements in balance, function and quality of life in patients with CAI.